Cover Image, Volume 76, Issue 7‐8. Issue 7 (19th November 2019) - Miyasaka, Yoshiya; Murakami, Keigo; Ito, Koji; Kumaki, Jiro; Makabe, Koki; Hatori, Kuniyuki
Abstract : ON THE COVER : The cover image is based on the Original Article Condensed desmin and actin cytoskeletal communication in lipid droplets by Kuniyuki Hatori et al., https://doi.org/10.1002/cm.21573 .